2006
DOI: 10.1159/000095959
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of CAY-1 with Amphotericin B and Itraconazole

Abstract: Background: CAY-1 is a fungicidal saponin from cayenne pepper whose mode of action differs from amphotericin B (AB) and itraconazole (IT). This work determined CAY-1 synergism with AB or IT. Methods: CAY-1 was purified and used in checkerboard microdilution studies where CAY-1 and AB or IT were mixed with nongerminated (NG) and germinating (G) conidia of three Aspergillus species and Candida albicans. Inhibition was visually determined at 24 and 48 h. Results: CAY-1 had predominantly additive-synergistic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 66%
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 66%
“…In addition, antifungal drugs can cause toxic or adverse drug reactions. For example, the polyene antifungal, amphotericin B, has a broad range of activity but is limited in its use due to numerous adverse effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…A previous report showed that CAY-1 (Fig. 1), a saponin from cayenne pepper (Capsicum frutescens), had fungicidal activities against Candida albicans and Aspergillus species [7].…”
Section: Introductionmentioning
confidence: 96%
“…CAY-1 also enhanced the activity of amphotericin B and itraconazole against the same organisms [7,8]. The aim of this study was to evaluate the in vitro activity of CAY-1 against both conidia and hyphae of dermatophytes, since it is not known whether the antifungal susceptibilities of these two morphological forms are similar.…”
Section: Introductionmentioning
confidence: 99%